Isolation of Housekeeping Genes on Durik-durik (Syzygium sp) - Roslim, Dewi Indriyani; Yusfi, Liza Aulia; Hutagalung, Desriani Ritawati; Faizah, Niswah; Andriani, Lestari; Azrial, Azrial; Herman, Herman; Lestari, Wahyu (Biosaintifika: Journal of Biology & Biology Education, 2018)
Housekeeping gene is a gene expressed with a fixed level and in abundant amounts under various conditions. After validation, the housekeeping gene can be used as an internal control to normalize gene expression data. This study reports the isolation of several housekeeping genes in Durik-durik plant (Syzygium sp). This plant material in form of fresh leaves from Durik-durik plants are taken from Kajuik Lake, Riau Province. The next stage is total DNA isolation, polymerase chain reaction, electrophoresis, sequencing and data analysis using bioinformatic tools. The isolated housekeeping genes included 18S rRNA, actin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Beta-tubulin and Ubiquitin with sizes of 400 bp, 679 bp, 1134 bp, 836 bp, 1167 bp and 2155 bp, respectively. In addition to 18S rRNA, the five housekeeping genes are the first reported from the genus Syzygium and referable to isolate housekeeping genes in other species in this genus. The six housekeeping genes can be used as internal controls on Durik-durik plants after validation.